P 150 The correlation of attention and neurophysiological characteristics in attention deficit hyperactivity disorder (ADHD). Issue 10 (October 2017) - Paucke, M.; Sander, C.; Hegerl, U.; Strauß, M.
Abstract : Scientific background/Introduction: Adult ADHD is a frequent psychiatric disorder which begins in childhood and persists into adulthood in up to 60% of the cases. As one pathogenetical mechanism the arousal regulation, which are measurable with EEG under rest, are discussed. The vigilance regulation model of affective disorders and ADHD interprets the hyperactivity and the sensation seeking behaviour as an autoregulatory and partly dysfunctional attempt of the organism to stabilize wakefulness (Hegerl and Hensch, 2014 ). Different EEG-studies confirm an instable EEG vigilance regulation in ADHD (Geissler et al., 2014 ) and show correlation with attention deficits (Sander et al., 2010 ). In the light of this results the correlation of EEG vigilance regulation as neurophysiological tonic arousal and attention deficits (measured by neuropsychological tests) in adult ADHD is investigated. Method: Adult ADHD patients and healthy controls were tested with the "Testbatterie zur Aufmerksamkeitsprüfung" (subtests alertness, working memory and Go/NoGo). EEG recordings of 15 min under quiet rest with eyes closed were performed. The computer-based Vigilance Algorithm Leipzig (VIGALL) was used to classify 1-s EEG segments into stages on the continuum ranging from full wakefulness to sleep onset. Findings: Group comparisons (ADHD vs. healthy controls) and correlational analysis were presented. Discussion: The investigated vigilance regulation model in ADHD could establish new insights into the neurophysiology of ADHD in adulthood.